(untitled) - Tanuja Bhatt (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Education must be well-designed and planned for the development of human capital. Educating teachers is therefore essential to meeting the needs and expectations at large. Educators should be taught and trained with different skills and knowledge to boost the education system. Apart from hard skills, the curricular approach of teacher education should give more emphasis on conceptual and soft skills abilities of teachers. This paper aims to explore the role and importance of soft skill training in teachers education. The study is based on secondary sources of information from various published data. At the end, the study concludes that soft skill is a vital skill needed for each and every future teacher for the overall development of students effectively.